Characterizations and product distribution of Co-based Fischer-Tropsch catalysts: A comparison of the incorporation manner. (15th May 2018) - Li, Zhuo; Wu, Liyang; Han, Dezhi; Wu, Jinhu
Graphical abstract: The consecutive hydrocracking of Co/SBA-15 primary hydrocarbons facilitated the formation of C5 -C11 on the Co/S15+Z5 catalyst with medium acid site, accordingly the selectivity of the C5 -C11 hydrocarbons was enhanced from 34% to 44%. The optimum dispersion of Co3 O4 and Co 2+ /Co 3+ ratio on the Co/(S15+Z5) catalyst facilitated the selective hydrogenolysis and the product distributions shifting to C12 -C22 with the increased selectivity from 27% to 40%. Highlights: The incorporation manner exerted significant effects on the catalytic performance. Co/S15 + Z5 facilitated the hydrocracking of heavier hydrocarbons to the C5 -C11 . Co/(S15 + Z5) was beneficial to the formation of C12 −C22 by selective hydrogenolysis. Co/(S15 + Z5) exhibited a high catalytic stability with time on stream for 120 h. Abstract: Co-based catalysts supported on SBA-15 and ZSM-5 were prepared by various incorporation manners and evaluated for the Fischer-Tropsch synthesis (FTS). The weight ratio of SBA-15 and ZSM-5 were 1:1 and Co had a constant loading of 15 wt% in all of the finished catalysts. Their physicochemical properties and catalytic performance were investigated by the N2 adsorption–desorption, XRD, TEM, XPS, NH3 -TPD, H2 - TPR, H2 -O2 titration, H2 -chemisorption and in a high pressure fixed-bed reactor, respectively. Characterizations indicated that the main cobalt species was Co3 O4 with small crystal size and high dispersion on the catalysts with SBA-15 as support, while the CoO with strong interaction with the support, as well as large particle size and low dispersion of Co3 O4 was observed on the ZSM-5 supported catalyst. It was found that the catalysts with SBA-15 as main support displayed superior CO conversion (85–90%) than the catalysts with Co species mostly deposited on the ZSM-5 support (∼70%), which was arise from the easy reduction of Co3 O4 with weak interaction with SBA-15 support. The consecutive hydrocracking of Co/SBA-15 primary hydrocarbons facilitated the formation of C5 -C11 on the Co/S15 + Z5 catalyst with medium acid site, accordingly the selectivity of the C5 -C11 hydrocarbons was enhanced from 51% to 62% in the liquid hydrocarbons. The optimum dispersion of Co3 O4 and Co 2+ /Co 3+ ratio on the Co/(S15 + Z5) catalyst facilitated the product distributions shifting to C12 -C22 with the increased selectivity from 41% to 52%. Furthermore, The superior catalytic stability for Co/(S15 + Z5) could be attributed to the synergistic effect of hydrogenolysis and cracking, which suppressed the coke deposition.